ANALYSIS OF PRODUCT PLACEMENT AS A GLOBAL MARKETING STRATEGY OF SUBWAY SANDWICH IN DRAMA MY ROOMMATE IS GUMIHO - Gabrielle Efan Hayatya Dewi; Resa Rasyidah (JRMSI - Jurnal Riset Manajemen Sains Indonesia, 2025)
Subway is a fast food restaurant from America that uses a franchise concept. This study aims to determine the Product Placement used by Subway Sandwich as a global marketing strategy in the Korean drama My Roommate is Gumiho. In this study, the author uses a qualitative method in social phenomena by collecting data from news, journals, articles, dramas, and books to find evidence that follows product placement and global marketing strategies. However, this study focuses on analyzing Korean dramas and news articles. The findings of this study will produce a division of product placement dimensions contained in the drama My Roommate is Gumiho. The result of this study is product placement carried out by Subway in the parts contained in the drama My Roommate, which means international audiences can increasingly recognize Subway products.